Bing himself : the story of Bing Crosby, the world's first multimedia star - Harris, Lauren R. (Amy Lane, 2025)
"Bing Himself introduces readers to the legendary Bing Crosby, the world's first multimedia star, whose remarkable career as a singer, actor, and influencer left an indelible mark on history. Written with a fact-driven narrative, the book shares authentic quotes from Bing himself, offering an accessible and inspiring look at his achievements. This book combines historical accuracy with stunning visuals, making it the perfect read for anyone who wants to explore the pioneers of entertainment." --Amazon.